A diversified and segregated mRNA spliced-leader system in the parasitic Perkinsozoa - Elisabet Alacid; Nicholas A. T. Irwin; Vanessa Smilansky; David S. Milner; Estelle S. Kilias; Guy Leonard; Thomas A. Richards (Open Biology, 2022)
Spliced-leader trans-splicing (SLTS) has been described in distantly related eukaryotes and acts to mark mRNAs with a short 5′ exon, giving different mRNAs identical 5′ sequence-signatures. The function of these systems is obscure. Perkinsozoa encompasses a diversity of parasitic protists that infect bivalves, toxic-tide dinoflagellates, fish and frog tadpoles. Here, we report considerable sequence variation in the SLTS-system across the Perkinsozoa and find that multiple variant SLTS-systems are encoded in parallel in the ecologically important Perkinsozoa parasite Parvilucifera sinerae. These results demonstrate that the transcriptome of P. sinerae is segregated based on the addition of different spliced-leader (SL) exons. This segregation marks different gene categories, suggesting that SL-segregation relates to functional differentiation of the transcriptome. By contrast, both sets of gene categories are present in the single SL-transcript type sampled from Maranthos, implying that the SL-segregation of the Parvilucifera transcriptome is a recent evolutionary innovation. Furthermore, we show that the SLTS-system marks a subsection of the transcriptome with increased mRNA abundance and includes genes that encode the spliceosome system necessary for SLTS-function. Collectively, these data provide a picture of how the SLTS-systems can vary within a major evolutionary group and identify how additional transcriptional-complexity can be achieved through SL-segregation.